Un catecismo fantasma: "El de Castilla" - Resines, Luis (Estudio agustiniano, 2025)
An information proceeding from 1586 shows a lot of catechisms used by Jesuits in Andalusia. Many of them are identified, but there is one, named "el de Castilla", their identification it is not possible with today investigations and knowledges.